Intervensi Berbasis Pasangan Pencegahan Sekunder dan Tersier Kekerasan dalam Rumah Tangga: Telaah Sistematis - Faiqa Himma Emalia; Yati Afiyanti; Imami Nur Rachmawati (Jurnal Keperawatan Padjadjaran, 2023)
Background: Intimate partner violence (IPV) is the most tragic form of gender inequality and has devastating effects on women worldwide. A couple/family-based intervention approach has been developed and tested to address obstacles preventing intimate partner violence. Purpose: This review aimed to examine couple-based interventions for secondary and tertiary intimate partner violence prevention. Methods: The researcher searched the electronic databases ProQuest, Scopus, PubMed, Science Direct, SpringerLink, and Taylor & Francis for relevant articles. This review includes English/Indonesian research articles published between 2012 and 2022. This study reviewed various types of secondary and tertiary intimate partner violence prevention interventions and their effectiveness in reducing the incidence of intimate partner violence against women. Risk of bias assessment was performed used A Revised Cochrane Risk of Bias Tools for Randomized Controlled Trial (RoB 2). Results: From the search findings, 1,819 articles were found, of which fifteen were included in the review, comprising twelve secondary preventive interventions and three tertiary prevention interventions make up these fifteen articles. Couple-based interventions for secondary prevention include gender transformative interventions, enhancing relationships with partners, bolstering the family economy, and encouraging men's participation in women's reproductive health and parenting. Cognitive-behavioral therapy predominates interventions for tertiary prevention to eliminate risk factors. Conclusion: This article recommends using couple-based interventions under the population's inherent risk factors and pays close attention to the safety of the implementation process.